Analisis Pengaruh Kemampuan Keuangan Daerah dan Kemandirian Keuangan Daerah Terhadap PDRB Perkapita Kota Banjarmasin - Hamiddah Lianita; Yunita Sopiana (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the ratio of regional financial capacity and the ratio of regional financial independence and their influence on GRDP per capita in Banjarmasin City. The data used in this study is secondary data consisting of data from the APBD and GDRP per capita of Banjarmasin City in 2010-2019. The analytical technique used is quantitative analysis by measuring the ratio and multiple linear regression. Analyzed using Eviews version 10 program.The results obtained from this study indicate that the regional financial capacity in Banjarmasin City in 2010-2019 is in the "moderate" category while regional financial independence in Banjarmasin City in 2010-2019 is included in the category of "adequate" relationship patterns. Regional financial capacity has a positive and significant impact on GDRP Percapita. Regional financial independence has a positive but not significant effect on GDRP per capita. Simultaneously, regional financial capability and independence have a positive and significant impact on GDRP Percapita.